Removal of singularities and Gromov compactness for symplectic vortices - Ott, Andreas (The journal of symplectic geometry, 2014)
We prove that the moduli space of gauge equivalence classes of symplectic vortices with uniformly bounded energy in a compact Hamiltonian manifold admits a Gromov compactification by polystable vortices.